Gas barrier plastic moldings
The gas barrier plastic molded body with an amorphous carbon film and specific H/C ratio maintains its gas barrier properties even after exposure to external forces, addressing the issue of property deterioration in flexible packaging applications.
Patent Information
- Application Number
- JP2021030473
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-26
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-02-26
AI Technical Summary
Existing gas barrier plastic molded bodies, such as those with DLC films, suffer from deterioration of gas barrier properties when exposed to external forces, particularly in flexible packaging applications like delami bottles.
A gas barrier plastic molded body with an amorphous carbon film on at least one surface, characterized by an H/C ratio of 0.75 or more and 1.00 or less, and an oxygen permeability of 5.0cc/m²/day or less, which maintains its gas barrier properties even after 160 bending tests with an increase ratio of less than 1.80.
The described gas barrier plastic molded body effectively suppresses the deterioration of gas barrier properties under external forces, making it suitable for flexible packaging applications without significant degradation in performance.
Smart Images

Figure 0007669718000003 
Figure 0007669718000004 
Figure 0007669718000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a gas barrier plastic molded article having an amorphous carbon film. [Background technology]
[0002] Conventionally, various packaging materials with high gas barrier properties have been used for various packaging materials for medical supplies, medicines, food, etc., in order to prevent deterioration of the contents due to oxygen, moisture, etc. For example, plastics with improved gas barrier properties are known by forming (1) a silicon compound film such as silicon oxide or silicon nitride, (2) an aluminum oxide film, or (3) an amorphous carbon (Diamond Like Carbon; DLC) film on the surface of the plastic. However, (1) gas barrier films coated with a silicon compound film have a problem that the silicon compound film is easily cracked due to stress such as bending and stretching of the film, which easily reduces the gas barrier properties, and therefore it is necessary to provide a primer layer on the base film. (2) gas barrier films coated with an aluminum oxide film have a problem that foreign body inspection using X-rays cannot be used, and the coating peels off when directly contacted with alkaline contents.
[0003] In contrast, the (3) DLC film is superior in that it has higher conformity to deformation of the plastic film and flexibility than the above-mentioned films (1) and (2), and can be used with an X-ray foreign body inspection machine. As plastic films on which such DLC films are formed, for example, technologies such as a pharmaceutical container film (Patent Document 1) in which a diamond-like carbon film having a hydrogen concentration of 50 atomic % or less and an oxygen concentration of 2 to 20 atomic % is formed on at least one side of the plastic film, and a diamond-like carbon film-coated gas barrier film in which the G-band intensity relative to the intensity of all peaks in Raman spectroscopy is 0.1 or less, the D-band intensity is 0.05 or less, and the coloring degree is 5.0 or less (Patent Document 2) have been disclosed.
[0004] In addition to the characteristics mentioned above, amorphous carbon (DLC) films also have strong resistance to acids and alkalis, and have been approved as a food contact material (FCN185) by the U.S. Food and Drug Administration (FDA) for safety and hygiene reasons. For this reason, they are formed on the inner surfaces of PET bottles and used as packaging containers for beverages, seasonings, and other products.
[0005] However, in recent years, there has been great progress in the development of delaminated bottles, an initiative aimed at extending food expiration dates and reducing food waste, but even the DLC films used to date have lacked flexibility. A delaminated bottle is a hollow plastic container (bottle) with a double structure consisting of a hard outer layer and a soft inner layer. The inner layer holds the contents, such as soy sauce, and when the body of the bottle is pressed, the contents are poured out. When the pressure is released, the shape of the outer layer returns to its original state but the shape of the inner layer does not return to its original state. This bottle has the following structure and function: it is possible to keep the contents fresh by preventing outside air from entering the inside of the inner layer. In other words, DLC films are formed on the inner surface of a bottle to exhibit gas barrier properties and are effective in preventing oxidation and spoilage of the contents; however, when a DLC film using the technology disclosed in Patent Document 1 or Patent Document 2 is applied to the inner surface of the inner layer of a delami bottle, the inner layer is pressed and deformed, damaging the DLC film and significantly degrading the gas barrier properties. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 11-070152 [Patent Document 2] JP 2008-229968 A Summary of the Invention [Problem to be solved by the invention]
[0007] In view of the above circumstances, the present invention provides a gas barrier plastic molded article which is capable of suppressing deterioration of its gas barrier properties even when subjected to an external force. [Means for solving the problem]
[0008] The present inventors have conducted extensive research into the above-mentioned problems and have completed the following invention. The first aspect of the present invention is to provide a plastic molded article having an amorphous carbon film on at least one of the front and back surfaces thereof, the H / C ratio of the hydrogen atom concentration to the carbon atom concentration being 0.75 to 1.00, and an oxygen permeability of 5.0 cc / m 2 / day or less, and the increase ratio of oxygen permeability after 160 bending tests is less than 1.80.
[0009] In the first aspect of the present invention, the plastic molded body is preferably made of a polyester resin.
[0010] In the first aspect of the present invention, it is preferable that the plastic molded body has a polyester-based resin layer on at least one of the front and back surfaces, and that the amorphous carbon film is provided on the polyester-based resin layer.
[0011] In the first aspect of the present invention, the plastic molded article is preferably a film or a hollow container. Effect of the Invention
[0012] The gas barrier plastic molded article of the present invention can suppress deterioration of the gas barrier properties even when subjected to an external force, and therefore can be suitably used for packaging such as bottles (delamination bottles) and bags in which the contents are pressed or squeezed out. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a schematic diagram illustrating a bending test. [Diagram 2]1 is an example of a polarizing microscope image of the surface of the amorphous carbon film of Comparative Example 2 after a 160-cycle bending test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Hereinafter, a gas barrier plastic molded body will be described as one example of an embodiment of the present invention, although the scope of the present invention is not limited to the embodiment described below. In addition, unless otherwise specified, the description "a to b" indicating a numerical range means "a or more and b or less," and also includes the meanings of "preferably greater than a" and "preferably smaller than b." Furthermore, even if the upper and lower limits of the numerical ranges in this specification are slightly outside the numerical ranges specified by the present invention, they are included in the equivalent range of the present invention as long as they have the same action and effect as those within the numerical range.
[0015] <Gas barrier plastic containers> The gas barrier plastic molded article of the present invention has an amorphous carbon film on at least one of the front and back surfaces of the plastic molded article. That is, the plastic molded article may have an amorphous carbon film on one of the front and back surfaces, or the plastic molded article may have an amorphous carbon film on both the front and back surfaces.
[0016] (amorphous carbon film) The amorphous carbon film in the gas barrier plastic container of the present invention contains carbon atoms and hydrogen atoms, and the carbon bonds are sp 3 Hybrid orbitals and sp 2 The film is a diamond-like carbon (DLC) film in which both hybrid orbitals are present. The lower limit of the H / C ratio of the hydrogen atom concentration to the carbon atom concentration is 0.75 or more, preferably 0.80 or more, and more preferably 0.85 or more. The lower the H / C ratio, the greater the sp 3 The higher the H / C ratio, the more sp 2The hybrid orbitals increase, and the flex resistance of the DLC film is improved. There is no particular upper limit to the H / C ratio, but from the viewpoint of gas barrier properties, it is preferably 1.00 or less, and the oxygen permeability of the gas barrier plastic molded body is preferably 5.0 cc / m 2 / day or less.
[0017] The carbon atom concentration and hydrogen atom concentration in the amorphous carbon film can be analyzed using a Rutherford backscattering spectrometer (RBS), with the carbon atom concentration being analyzed by nuclear reaction analysis (NRA) and the hydrogen atom concentration being analyzed by elastic recoil detection analysis (ERDA) and hydrogen forward scattering (HFS).
[0018] The amorphous carbon (DLC) film can be formed on the surface of a plastic molded body by using a known plasma chemical vapor deposition method. The plastic molded body may be preliminarily heat-treated to volatilize low molecular weight components, or the surface may be plasma-treated. Examples of the raw material gas include unsaturated hydrocarbon compounds such as acetylene, ethylene, and propylene; saturated hydrocarbon compounds such as methane, ethane, propane, and cyclohexane; and aromatic hydrocarbon compounds such as benzene, toluene, and xylene. These may be used alone or in combination of two or more. Among these, it is preferable to use ethylene or acetylene gas because the ratio of hydrogen atoms to carbon atoms in the raw material gas chemical formula is low.
[0019] In order to increase the H / C ratio of the hydrogen atom concentration to the carbon atom concentration of the amorphous carbon (DLC) film, it is preferable to mix and use hydrogen and a gas with a high ratio of hydrogen atoms to carbon atoms in addition to the above-mentioned raw material gas. For example, when acetylene gas and hydrogen gas are mixed and used, the flow rate (sccm) ratio of hydrogen gas to acetylene gas is preferably 1.0 or more, more preferably 1.1 or more, and even more preferably 1.2 or more. There is no particular upper limit, but from the viewpoint of gas barrier properties and film formation speed, it is preferably 1.5 or less. In addition, by relatively lowering the power output during film formation, decomposition of the source gas is suppressed and a film closer to a polymer is formed, which makes it possible to increase the H / C ratio. It is also effective to keep the temperature of the substrate low during film formation by cooling, etc. This is because DLC generally tends to turn into graphite rather than diamond at temperatures above 350°C, so by keeping the temperature below this level, the H / C ratio can be increased. When using a resin as the substrate, the temperature is preferably 100°C or lower, taking into account its melting point, and more preferably 50°C or lower.
[0020] In the plasma chemical vapor deposition method, evacuation (reducing pressure) and gas introduction are performed, and when the inside pressure (degree of vacuum) reaches a certain level, the raw material gas is converted into plasma to form a film. The internal pressure during film formation is preferably 1 Pa or more and 50 Pa or less, taking into account the balance between good film quality and physical properties and the time required for film formation. When the plastic molded body is in the form of a film, it is advisable to use a plasma chemical vapor deposition apparatus in which a film is disposed between flat plate electrodes. As exemplified in JP-A-11-070152, a substrate is placed on one side of parallel plate electrodes provided in a vacuum apparatus, and the inside of the vacuum apparatus is evacuated until the pressure is 1 Pa or less. Thereafter, a raw material gas is supplied via a mass flow controller or the like, and the pressure is adjusted to about 1 to 50 Pa. In the case of DLC, a hydrocarbon gas is used as the raw material gas, and one or a mixture of multiple gases is used. After the pressure becomes constant, a high-frequency power is applied by a high-frequency power source, plasma is generated, and a film is formed on the surface of the substrate. In this case, the frequency of the high-frequency is generally 13.56 MHz, which is a commercial frequency, but it is also possible to change the frequency depending on the size of the apparatus, the type of gas, and the like. In this case, it is usually 4 kHz to 100 MHz, preferably 4 kHz to 13.56 MHz. Discharge is maintained for a time until the expected film thickness is deposited, and film formation is continued.
[0021] When the plastic molded body is a hollow container (bottle), a plasma chemical vapor deposition apparatus is used in which an external electrode is arranged around the bottle and an internal electrode and a source gas inlet are installed inside the bottle, as typified by JP-A-8-53116. The chamber is made to have a predetermined degree of vacuum, a source gas is supplied, and a voltage is applied between the external electrode and the internal electrode at ground potential to generate plasma inside the container housed in the external electrode, thereby forming a gas barrier film on the inner surface of the container. For example, when a high-frequency power source is used as the power source, the frequency can be several MHz or more and several hundred MHz or less, and from the viewpoint of versatility, it can be preferably 6 MHz or 13.56 MHz. The film formation time can be, for example, 0.2 to 20 seconds, preferably 1.0 to 10 seconds.
[0022] (Plastic Molded Body) The plastic molded article used in the present invention is not particularly limited in shape as long as it has a pair of a front surface and a back surface, and is preferably a film or a hollow container (bottle) from the viewpoint of use in packaging applications. In the case of a film, one surface is the front surface and the other surface is the back surface, and in the case of a hollow container, the outer surface of the bottle is the front surface and the inner surface of the bottle is the back surface. The film may be unstretched, uniaxially stretched, or biaxially stretched, with biaxial stretching being preferred from the standpoint of mechanical strength, and the stretching ratio being preferably 2.0 to 5.0 times in both the longitudinal and transverse directions. The layer structure may be single-layered or multi-layered. From the standpoints of mechanical strength and economy, the thickness is preferably 5 to 100 μm, more preferably 8 to 50 μm, and even more preferably 10 to 25 μm. The film on which the amorphous carbon film is formed is laminated with a sealant film or the like and processed into a package such as a bag. The hollow container may be formed by either injection molding or blow molding, and from the viewpoints of mechanical strength and heat resistance, blow molding with effective stretch orientation is preferred, and the areal stretch ratio is preferably 6 to 14 times. Alternatively, the container may be a multi-layer bottle having an outer layer and an inner layer, such as a delaminated bottle. In the case of a multi-layer bottle, it is preferable to form an amorphous carbon film on the inner layer, and it is more preferable to form an amorphous carbon film on the inner surface of the inner layer.
[0023] The composition of the plastic molded body is not particularly limited, but examples thereof include polypropylene-based resins such as homopolypropylene and ethylene-propylene copolymer, polyester-based resins such as polyethylene terephthalate, polyethylene naphthalate, and polybutylene terephthalate, polyamide resins, and polycarbonate-based resins. From the standpoint of heat resistance and versatility, polyester-based resins are preferred, and of these, polyethylene terephthalate is preferred. When the plastic molded article is multi-layered, a coextruded multi-layer is preferable, and examples of the layer configuration include a multi-layer of polyester resins having different compositions, a multi-layer of polypropylene resin / polyester resin, and a multi-layer of polyolefin resin / polyamide resin / polyester resin, and an adhesive resin layer such as a thermoplastic elastomer may be disposed between the above-mentioned resin layers to improve adhesion between the layers. Also, when the plastic molded article is multi-layered, it is preferable that at least one of the front and back surfaces of the plastic molded article has a polyester resin layer, and that an amorphous carbon film is formed on the surface of the polyester resin layer.
[0024] (Gas barrier properties) The gas barrier plastic molded article of the present invention has an oxygen permeability of 5.0 cc / m 2 / day or less, 4.0cc / m 2 / day or less is preferable, and the lower the value, the better the gas barrier properties are. Oxygen permeability When the plastic molded body is a film, the oxygen transmission rate is measured using a MOCON Oxtran 2 / 22 machine at a temperature of 23°C and a relative humidity of 0%. When the plastic molded body is a hollow body (bottle), the oxygen transmission rate (unit: cc / pkg / day) is measured using a MOCON Oxtran 2 / 21 machine equipped with a ball plug adapter at a temperature of 23°C and a relative humidity of 50%, and the unit is converted using the inner surface area of the hollow container (bottle).
[0025] - Bending test, film surface observation In general, gas barrier plastic molded articles are processed into packaging that contains contents, and as the packaging is used, the plastic molded articles are deformed by external forces, and the gas barrier properties gradually or suddenly deteriorate. In particular, silicon compound films such as silicon oxide and silicon nitride are hard, and the defects are likely to be prominent. In contrast, amorphous carbon (DLC) films are known to have flexibility, but in applications such as pouches and delaminated bottles, where the packaging is pressed or the contents are squeezed, the suppression of the deterioration of the gas barrier properties due to deformation is insufficient. In this regard, the gas barrier plastic molded article of the present invention has the characteristic of being able to suppress the deterioration of the gas barrier properties. This is because the amorphous carbon film of the present invention has many bonds between carbon and hydrogen in the film, which gives the film high flexibility and makes it less likely to crack.
[0026] To evaluate the flexibility of the film and the inhibition of deterioration of the gas barrier property, if the plastic molded body is a film, the following bending test is carried out, and the oxygen permeability is measured and the film surface is observed. In the bending test according to the present invention, an amorphous single layer (DLC) film is formed on one surface of a film having a width of 170 mm and a length of 240 mm, the film-formed film 10 is placed on a flat plate 40 with the DLC film facing upward, and a glass rod 30 having a diameter of 5 mm is placed on the film 10 in parallel with the width direction of the film 10. The bending test is counted as one bending by placing the film-formed film 10 halfway around the glass rod 30 in the circumferential direction and then returning it to the horizontal direction. The bending test was performed 60 times and 160 times (FIG. 1(a) shows the state in which the glass rod 30 is placed on the film-formed film 10 on the flat plate 40, and FIG. 1(b) shows the state in which the film-formed film 10 is placed halfway around the glass rod 30 in the circumferential direction). The ratio (increase ratio) of oxygen transmission rate of the 160 times bending test sample to the unbent sample is less than 1.80, preferably 1.60 or less, more preferably 1.50 or less.
[0027] The film surface was observed before and after the bending test with the DLC film facing upwards, and a polarizing microscope was used to observe the film at a magnification of 1000x and a viewing angle of 325μm×240μm, and the number of cracks with a length of 25μm or more was counted. Observations were performed at two locations, and the number of cracks counted was averaged to determine the number of cracks with a length of 0.1mm or less. 2 The number of cracks after 160 bending tests was 5.0 / 0.1 mm. 2 Less than 3.0 pieces / 0.1mm is preferable. 2 Less than 2.0 pieces / 0.1mm is more preferable. 2 More preferably, the number of cracks having a length of 10 to 25 μm is 1.0 per 0.1 mm. 2 It is preferable that:
[0028] When the plastic molded body is a hollow container (bottle), a bending test can be performed, for example, by cutting out a specific width from the cylindrical body of the bottle in the circumferential direction to prepare a test piece, and performing a bending test in the same manner as for a film to evaluate the test piece. Also, for example, a bending test can be performed in which the body of the bottle is pressed from the outside to the inside and then released, for evaluation. EXAMPLES
[0029] The present invention will be described below with reference to examples and comparative examples, but the present invention is not limited to these examples. <Example 1, Comparative Examples 1 and 2> A 50 μm thick biaxially stretched polyethylene terephthalate monolayer film was used as an adherend, and a 100 nm thick DLC film was formed on one surface of the film using a plasma CVD film forming apparatus to obtain a film-formed film. DLC film formation was performed according to the following procedure and conditions. First, a film was placed on one of parallel plate electrodes with an interelectrode distance of 130 mm, and the pressure was reduced to 1 Pa or less. After reducing the pressure, the raw material gas flow rate shown in Table 1 was introduced into the apparatus via a mass flow controller, and a high-frequency power of 200 W or 500 W with a frequency of 13.56 MHz was applied. The pressure during film formation was 1 to 8 Pa. The film formation time was set by investigating the conditions for a film thickness of 100 nm for each raw material gas condition in Example 1 and Comparative Examples 1 to 2 in advance, and the film formation time shown in Table 1 was set. In addition, the plate electrode on which the film was placed was cooled, and film formation was performed in a state where the film temperature was 50° C. or less. The obtained film was used to carry out the above-mentioned bending test, oxygen permeability measurement, and film surface observation, and the results are summarized in Table 2. In addition, "untested ratio" in Table 2 means "the ratio (increase ratio) of oxygen permeability of the bent test sample to the unbent test sample."
[0030] In addition, a DLC film was formed on a silicon wafer as an adherend using the above-mentioned plasma CVD apparatus under the same film formation conditions as in Example 1 and Comparative Examples 1 and 2. The carbon atom concentration and hydrogen atom concentration of the DLC film were analyzed using a Rutherford backscattering spectrometer (RBS), with the carbon atom concentration being analyzed by nuclear reaction analysis (NRA) and the hydrogen atom concentration being analyzed by elastic recoil detection analysis (ERDA). NRA used deuterons (D+) with an energy of 0.98 MeV as the incident ion species, and analysis was performed at a detector installation angle of 150°, and the carbon atom concentration in the DLC film was analyzed by comparing it with the peak area of a standard sample. ERDA used helium ions (4He+) with an energy of 2.0 MeV as the incident ion species, and analysis was performed at a detector installation angle of 30°, and the hydrogen atom concentration in the DLC film was analyzed using the simulation software SIMNRA ver.6.03. The obtained carbon atom concentration (C concentration), hydrogen atom concentration (H concentration), and atomic concentration ratio (H / C) are summarized in Table 1.
[0031] [Table 1]
[0032] [Table 2]
[0033] In Example 1, hydrogen gas was used as the source gas at a flow rate 1.25 times that of acetylene gas, and the H / C ratio of the hydrogen atom concentration to the carbon atom concentration of the DLC film was 0.75 to 1.00. As a result, the oxygen permeability of the deposited film was 5.0 cc / m 2 / day or less, and the increase ratio of oxygen permeability after 160 bending tests was less than 1.80, which means that the deterioration of gas barrier properties was suppressed. In addition, the number of cracks with a length of 25 μm or more after the bending test was 2.0 / 0.1 mm. 2 The bending resistance was remarkably good. Comparative Example 1 is an example in which a small amount of hydrogen gas was used. The H / C ratio was higher than that of Comparative Example 2, but the increase ratio of the oxygen permeability after 160 bending tests was 1.80, there were many cracks, and the bending resistance was insufficient, close to Comparative Example 2 in which no hydrogen gas was mixed. 2 shows a polarizing microscope image of cracks on the DLC film surface after a 160-cycle bending test in Comparative Example 2. It can be seen that there are many cracks with lengths of 25 μm or more. [Industrial Applicability]
[0034] The gas barrier plastic molded article of the present invention is suitable for packaging such as hollow containers (bottles) and bags. For example, when squeezed into delaminated bottles or retort pouches, the gas barrier properties are less deteriorated and the contents can be kept fresh for a long period of time. Therefore, it is useful for reducing food waste. [Explanation of symbols]
[0035] 10: Deposition film 30: Glass rod 40: Flat plate
Claims
1. The plastic molded body has an amorphous carbon film on at least one of the front and back surfaces, the H / C ratio of the hydrogen atom concentration to the carbon atom concentration being 0.75 or more and 1.00 or less, Oxygen permeability is 5.0cc / m 2 / day or less, and the increase ratio of oxygen permeability after 160 bending tests is less than 1.80, 1. A gas barrier plastic molded article, comprising a film processed into a packaging material for a bag.
2. 2. The gas barrier plastic molded article according to claim 1, wherein the plastic molded article is made of a polyester resin.
3. 2. The gas barrier plastic molded article according to claim 1, which has a polyester-based resin layer on at least one of the front and back surfaces of the plastic molded article, and has the amorphous carbon film on the polyester-based resin layer.
4. A method for producing the gas barrier plastic molded body according to claim 1, comprising: a method for producing a gas barrier plastic molded body, the method comprising: forming the amorphous carbon film on the surface of the plastic molded body by using a plasma chemical vapor deposition method, and using hydrogen gas and a source gas consisting of one or more compounds selected from the group consisting of unsaturated hydrocarbon compounds, saturated hydrocarbon compounds, and aromatic hydrocarbon compounds, such that the flow rate (sccm) ratio of the hydrogen gas to the source gas is 1.1 or more.
5. A method for producing a gas barrier plastic molded body as described in claim 4, wherein the amorphous carbon film is formed by setting the surface temperature of the plastic molded body to 100°C or lower.
Citation Information
Patent Citations
Film for pharmaceutical container
JP1999070152A
Dlc film and carbon film coated plastic container
JP2001232714A
Plastic container for liquid containing volatile organic substance
JP2001240034A
Discharging container
JP2008162666A
Gas-barrier film coated with diamond-like carbon film
JP2008229968A